Vorstand der Jüdischen Gemeinde Newsletter, October 1935 - Vorstand der Jüdischen Gemeinde (1935)
The Director of the Jewish Community in Berlin informs community members that Jewish citizens are no longer allowed to participate in the Winter Relief Organization due to new regulations created by the Third Reich.
Keywords: Vorstand der Jüdischen Gemeinde; Antisemitism; Third Reich; Jews, German